The blue light signal transduction module FaCRY1-FaCOP1-FaHY5 regulates anthocyanin accumulation in cultivated strawberry - Liu, Yongqiang; Tang, Li; Wang, Yiping; Zhang, Lianxi; Xu, Shiqiong; Wang, Xiao; He, Wen; Zhang, Yunting; Lin, Yuanxiu; Wang, Yan; Li, Mengyao; Wang, Xiaorong; et al. (Frontiers in Plant Science, 2023)
Anthocyanins have important physiological functions and are beneficial to the improvement of fruit quality in strawberry. Light is indispensable for anthocyanin biosynthesis, and specific light quality was identified to promote anthocyanin accumulation in many fruits. However, research on the molecular mechanisms of anthocyanin accumulation regulated by light quality in strawberry remains limited. Here we described the effects of red- and blue-light irradiation on anthocyanin accumulation in strawberry. The results showed that blue light, rather than red light, could lead to the rapid accumulation of anthocyanins after exposure to light for 48 hours. The transcriptional levels of anthocyanin structural and regulatory genes displayed similar trend to the anthocyanin content. To investigate the mechanism of blue light-induced anthocyanin accumulation, the homologs of Arabidopsis blue light signal transduction components, including the blue light photoreceptor FaCRY1, an E3 ubiquitin ligase FaCOP1 and light-responsive factor FaHY5, were cloned from the strawberry cultivar ‘Benihoppe’. The protein-protein interaction of FaCRY1-FaCOP1-FaHY5 was revealed by yeast two-hybrid and fluorescence signal assays. Functional complementation analysis showed that overexpression of either FaCOP1 or FaHY5 restored the anthocyanin content and hypocotyl length in corresponding Arabidopsis mutants under blue light. Moreover, dual-luciferase assays showed that FaHY5 could increase the activity of FaRAP (anthocyanin transport gene) promoter and that this function relied on other, likely B-box protein FaBBX22, factors. The overexpression of FaHY5-VP16 (chimeric activator form of FaHY5) and FaBBX22 promoted the accumulation of anthocyanins in transgenic strawberry plants. Further, transcriptomic profiling indicated that the genes involved in the phenylpropanoid biosynthesis pathway were enriched in both FaHY5-VP16-OX and FaBBX22-OX strawberry plants. In summary, our findings provide insights into a mechanism involving the regulation of blue light-induced anthocyanin accumulation via a FaCRY1-FaCOP1-FaHY5 signal transduction module in strawberry.